PERANCANGAN PERHIASAN TERINSPIRASI DARI BUNGA KAMBOJA SEBAGAI BUNGA IDENTITAS AGAMA HINDU DI PULAU BALI - THALIA MIRANDA SOEDARMADJI; Markus Hartono; Kumara Sadana Putra (Perpustakaan Universitas Surabaya, 2018)
Abstract - Jewelry today is a secondary requirement in the field of fashion, it becomes an opportunity for jewelry archipelago to further develop and promote business. Similarly for Bali, as one of the main tourist destinations in Indonesia, so many domestic and foreign tourists who come to do the holidays. Jewelry itself in Bali is very easy to find but for the existing designs in the community is a traditional design and do not keep up with the times, therefore I take the opportunity in the modern jewelry sector that still uses the symbol or characteristic of Bali itself like frangipani Bali. Flowers used by the Hindu people in prayer. The purpose of this design to lift Balinese frangipani flowers become more iconic and known as inspiration jewelry design that is universal.